ENHANCING READING SKILLS: STRATEGIES FOR STUDENT SUCCESS - Baxtiyorova Lola Otabekovna (Лучшие интеллектуальные исследования, 2024)
Annotation. This comprehensive article explores effective strategies for improving reading skills among students, emphasizing the importance of cultivating a culture of reading both inside and outside the classroom. Drawing on research-based practices and practical examples, the author highlights ten key approaches to enhance reading proficiency, including encouraging regular reading, providing explicit instruction, and promoting active engagement with texts. The article underscores the significance of differentiated instruction to meet the diverse needs of learners and emphasizes the integration of technology and cross-curricular connections to reinforce literacy skills across disciplines. Overall, this resource serves as a valuable guide for educators seeking to create engaging and effective reading instruction that fosters a lifelong love of reading among students.